Caracterização química, avaliação da toxicidade e atividade cicatrizante de feridas do extrato aquoso do infuso das folhas de Sorocea guilleminiana Gaudich. - Figueiredo, Fabiana de Freitas (2018)
Sorocea guilleminiana, Moraceae, popularly known as “espinheira-santa-falsa”, is a native and endemic Brazilian shrub found in the Cerrado and Atlantic forest, whose infusion of leaves is popularly used to treat wounds, infection, gastritis, kidney disease and inflammation. The objective of this study was to evaluate the toxicity and wound healing activity of the aqueous extract of S. guilleminiana leaf infusion (AESg) in experimental models in vivo and in vitro. The AESg was prepared by infusion, the leaves powder was mixed in boiling water (10 g/L) for 15 min. Phytochemical analyzes were performed by thin layer (TLC) and high performance liquid chromatography (HPLC). Cytotoxicity in Chinese hamster ovary epithelial cells (CHO-K1) and cell viability of AESg in N3T3 fibroblasts (6.25 - 800 μg/mL) were assessed by flow cytometry. The genotoxicity of AESg (10, 30 and 100 μg/mL) was evaluated in CHOK1 cells by the micronucleus (MN) and comet (COM) tests. The evaluation of AESg (0.8, 4 and 20 μg/mL) on proliferation/migration was performed in a monolayer scratch test in N3T3 cells. For acute toxicity assessment, single oral administration of AESg (up to 2000 mg/kg) in Swiss-Webster mice was performed. The wound healing activity of the AESg was evaluated in the excision and incision wound models in Wistar rats. The wound healing mechanism of action of the AESg was assessed through the evaluation of activity of myeloperoxidase (MPO) and catalase (CAT) and by the determinations of the levels of glutathione (GSH), cytokines TNF-α, IL-1β, IL-17, IL-12p70, and IL-10 using the incision wound model. Preliminary phytochemical analyzes of the crude extract revealed the presence of flavonoids, steroids and terpenes. No changes were observed regarding cytotoxicity, viability, as well as absence of genotoxicity by MN test. In the COM test, pre-treatment with AESg prevented DNA damage at the three concentrations tested (p<0.001), while co-treatment reduced the damage only at the lowest concentration (p<0.001). Post-treatment with AESg reduced the genetic damage induced by hydrogen peroxide in the lowest and highest concentration (p<0.001). AESg (0.8, 4 and 20 μg/mL) increased proliferation/migration of N3T3 cells (p<0.001). In the excision wound model, AESg (2 and 50 mg/g) increased the rate of wound contraction on the 5 th , 7 thand 9thday (p<0.05), while Fitoscar® (60 mg/g), standard for this experiment, increased the rate of contraction at day 9 (p<0.05). There was no change in the re-epithelialization period at any dose tested. In the incision wound AESg (2 and 50 mg/g) was increased (p<0.01) tissue resistance to traction. AESg (2, 10 and 50 mg/g) and Fitoscar® (60 mg/g) reduced the MPO activity (p<0.001). AESg at doses of 2 and 50 mg/g was increased levels of GSH (p<0.05) and CAT (p<0.01). AESg did not alter the levels of TNF-α, IL-1β, IL-17 and IL-10, however, AESg at 50 mg/g increased (p<0.05) IL-12p70 levels. It can be stated that AESg is safe when administered orally in a single dose, does not present cytotoxicity and genotoxicity in the models tested, and antigenotoxic potential is suggested. These results confirm the popular use of infusion of S. guilleminiana for treatment of cutaneous wounds, probably because it stimulates the proliferation of fibroblasts with consequent deposition of collagen and transformation in myofibroblasts are essential in the process of wound healing, due to its antioxidant effect, possibly exerted by phenolic compounds.